2018
DOI: 10.15625/0866-7187/40/2/12266
|View full text |Cite
|
Sign up to set email alerts
|

Seismic status in Bangladesh

Abstract: Seismic status in Bangladesh has been investigated using earthquake data recorded by the global network of USGS during 1980 to 2016. Seismicity parameters such as magnitude completeness Mc, b-value and a-value are being estimated. It has observed that the overall b-value in and around Bangladesh is of 0.84 which is seemed to be seismically active zone. As, reliable b-value assessment can lead to better seismic hazard analysis, reliable magnitude of completeness Mc can lead to b-value assessment of an area, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Khan et al (2011) found b values in NE India (24.5-25.2°N and 90-90°E) for zone I, where the b value varies from 0.5-0.7. Likewise, Rahman et al (2018) observed that the b value was within the range of 0.77-1.15. Nevertheless, the variability of the seismicity rate across the whole of India and adjoining areas was observed as the b values in the range of 0.7-0.8 (Kolathayar et al 2012).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Khan et al (2011) found b values in NE India (24.5-25.2°N and 90-90°E) for zone I, where the b value varies from 0.5-0.7. Likewise, Rahman et al (2018) observed that the b value was within the range of 0.77-1.15. Nevertheless, the variability of the seismicity rate across the whole of India and adjoining areas was observed as the b values in the range of 0.7-0.8 (Kolathayar et al 2012).…”
Section: Discussionmentioning
confidence: 88%
“…Recent studies have revealed almost identical measurements of magnitude of completeness in the studied area. Rahman et al (2018) observed that the estimated M C value was 3.9-4.7 and the overall b value in and around Bangladesh was 0.84. Similarly, Kolathayar et al (2012) found that M C varied from 4.25 to 4.5 for in and around Bangladesh region.…”
Section: Discussionmentioning
confidence: 96%
“…There are seven faults and thirteen lineaments, which might worsen the disaster situation if any earthquake of 4/5 Richter scale occurs in the adjacent area (Ahmad, 2014). The western part of the DCC, from Mirpur-Kallyanpur-Pagla along River Buriganga, and the areas from Uttar Khan-Badda-Demra along the River Balu in the eastern region are the High-Risk Zones of earthquakes (Rahman, et al, 2018, Hussaini, et al, 2015, and Shaha, 2015. The anthropogenic activities such as unplanned land use patterns, depletion and blockage of natural water bodies, violation of geomorphic features, inappropriate industrial waste treatment plants, and other toxic emissions from the vehicles, industries, and brick kilns in the DCC aggravate the magnitude and frequency of geo-environmental disasters.…”
Section: Geo-environmental and Anthropogenic Disastersmentioning
confidence: 99%
“…As a result, there was an error in the estimation of the seismicity parameters by nearly 0.2. A detailed study of the completeness magnitude of Bangladesh done by Rahman et al (2018) showed the contours of 'a' and 'b' values. Later more reliable completeness period of Pakistan using the Stepp (1972) method was done by Waseem (2021) changing bin width of magnitude.…”
Section: Introductionmentioning
confidence: 99%